Kuliah Kerja Nyata dalam Meningkatkan Pola Pikir Masyarakat dalam Pemanfaatan Sumber Daya Alam: Pelatihan Pembuatan Anyaman Bengkuang - Ifnaldi, Ifnaldi; Harnedi, Joni; Evina, Titra (Al-DYAS, 2022)
Real Work Lecture (KKN) is an activity based on community empowerment with a multi-disciplinary approach that seeks to overcome social problems that exist in society. Therefore, the implementation begins with the initial socialization (soswal) which is carried out with the village head, is the initial process to find out the activities that exist in the local community. This initial socialization activity (Soswal) is important to formulate an activity plan as an alternative problem solving which will be followed up on a discussion with the community for the design of activities for Making Weaving from yam leaves.